An exploration of clinical learning experiences of higher diploma nursing students at a tertiary referral hospital in Kenya - Kipsoi, Mary Jebichii; Wachira, Serah Wanjiru; Esho,Tammary (Pan African Medical Journal, 2025)
Introduction: clinical learning experiences are critical in shaping nursing students’ competency and confidence. Despite comprehensive theoretical instruction, challenges persist in translating knowledge into practice, particularly in high-pressure clinical environments. An evaluation at a tertiary referral hospital revealed that many Higher Diploma nursing students felt unprepared for clinical evaluations and struggled with practical skills, yet limited local research exists to explore these experiences. The study aimed to explore the clinical learning experiences for Higher Diploma Nursing Students at Kenyatta National Hospital, Kenya. Methods: a qualitative descriptive design was employed. A purposive sample of 24 Higher Diploma nursing students participated in individual in-depth interviews (n=12) and two focus group discussions (n=12). Data were collected using a semi-structured interview guide and were analyzed thematically using a six-step process, ensuring adherence to trustworthiness principles, including credibility and confirmability. Results: three major themes emerged: The first was personal challenges and triumphs, with most participants reporting struggles related to work-life balance, health issues, and financial constraints. The second theme focused on institutional support mechanisms, as over half of the students described inconsistent mentorship, unclear policies, and limited access to learning resources. The third theme involved the clinical learning environment, where many students experienced overcrowded settings, emotional insecurity, and stress related to workload. These factors collectively influenced students’ engagement and learning outcomes during clinical placements. Conclusion: clinical learning experiences among higher diploma nursing students are shaped by the interplay of personal, institutional, and environmental factors. Tailored support systems, structured mentorship, and learner-centered policies are essential to enhancing the clinical learning environment. Further research is recommended to assess how these factors impact learning outcomes and professional development.
Keywords: Clinical learning; experience; higher diploma nursing